Rediscovery of Southern Barbed-wire Bush-cricket, Onconotus servillei Fischer von Waldheim (Orthoptera: Tettigoniidae: Tettigoniinae: Onconotini) in Serbia, with notes on species’ calling song at the westernmost border of its distribution area - Ivković, Slobodan; Horvat, Laslo; Iorgu, Ionuț Ștefan (Zootaxa, 2020)
Described from Odessa and North Caucasus, the Southern Barbed-wire Bush-cricket, Onconotus servillei Fischer von Waldheim (1846) has a distribution restricted to steppe habitats in Eastern Europe, European Russia up to Western Siberia (Fig. 1A) (Storozhenko 1994; Cigliano et al. 2019).